Kompetenzverteilung in der Agrarpolitik in Deutschland - Carsten Thoroe (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– (Re-)Distribution of responsibilities in agricultural policy in Germany: In agricultural policy in Germany institutional and functional spheres of responsibility are mixed. The constitution of the Federal Republic of Germany warrants a strong position to the federal states in relation to the federal government. But in fact, the decentralized lines of the constitutional law and the clear division of responsibilities between the federal government and the federal states have lost their contours over time. Taking the developments on the revenue side and the expenditure side together, in the national sphere in Germany there is the impression that the various governmental levels form a sturdy "network". Only at the level of implementation there are quite pronounced decentralized elements. There has been much critical discussion since the late 1970s of this co-operative federalism, the result of the networking of government levels. However, it has not been changed in principle. In the field of agricultural policy this networking is superimposed by the incorporation of the EU. Against the background of changed underlying conditions for integration and increased integration of European agriculture in world trade, the extensive transfer of agricultural policy responsibilities to the EU is in need of revision. In particular, the opening of the EU towards Central and Eastern Europe also requires a consideration of the mechanism of the EU agricultural policy. Recommendations from the viewpoint of fiscal federalism are discussed for a revision in competences and clear demarcation of responsibilities for different fields of agricultural policy.
Keywords: 330; Agrarpolitik; Deutschland